Strategi Pengelolaan Lingkungan Dalam Penerapan Ekonomi Hijau Pada Pt Pertamina Patra Niaga Tbk - Alinda Dwi Jofanka; Ida Bagus Ketut Bayangkara (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
This research aims to understand the environmental management strategy in implementing the green economy at PT Pertamina Patra Niaga Tbk using descriptive qualitative methods. The data that is the focus of the analysis comes from official company documents, including sustainability reports and annual reports for the period 2022. Document analysis is carried out to identify data that is relevant to the research problem while ensuring the accuracy of the data. The research results confirm that PT Pertamina Patra Niaga Tbk shows a strong commitment to the green economy concept by integrating environmentally friendly practices into all aspects of its business. The company's primary focus lies on strategies to reduce greenhouse gas emissions and responsible waste management to reduce environmental impact, while also focusing on the efficient use of natural resources and the development of environmentally friendly products and services to support the transition to a clean economy.